Kepemimpinan Visioner Kepala Madrasah dalam Meningkatkan Brand Awareness Quality di Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Dwi Febriani; An An Andari; Cipto Handoko (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to analyze in depth how the visionary leadership of the madrasah principal plays a role in increasing brand awareness quality of Madrasah Aliyah Hidayatul Mubtadiin Jati Agung South Lampung through strategic, symbolic, and contextual leadership practices. This study uses a qualitative approach with a case study design to understand the role of the visionary leadership of the principal of Madrasah Aliyah Hidayatul Mubtadiin Jati Agung in building brand awareness quality. The research subjects were selected purposively, including the madrasah principal, teachers, education staff, students, parents, and community leaders. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed thematically. Data validity was maintained through triangulation of sources and techniques. The results of this study indicate that the visionary leadership of the principal of Madrasah Aliyah Hidayatul Mubtadiin Jati Agung South Lampung plays a strategic role in building brand awareness quality through strategic, symbolic, and contextual practices. Strategic leadership strengthens the quality identity of the madrasah through superior programs, service quality, and structured internal management. Institutional symbols and culture, such as discipline, dress code, exemplary behavior, and academic and religious activities, strengthen public perceptions of madrasah quality. Furthermore, contextual relationships with parents, community leaders, and local stakeholders broaden recognition of quality and enhance public trust. The findings confirm that the combination of visionary leadership practices and social interactions fosters sustainable brand awareness of quality, enhances reputation, and strengthens the madrasah's standing in the community.